Emotional overactivity in patients with irritable bowel syndrome. Issue 10 (1st June 2018) - Fournier, A.; Mondillon, L.; Dantzer, C.; Gauchez, A.‐S.; Ducros, V.; Mathieu, N.; Faure, P.; Canini, F.; Bonaz, B.; Pellissier, S.
Abstract: Background: Negativity is often observed in patients with irritable bowel syndrome (IBS). No study has examined their emotional expressiveness as a marker of emotional reactivity. We investigated IBS patients' vulnerability to an emotional load by associating their expressiveness with psychological and neurophysiological assessments. We hypothesized that IBS would be characterized by a lack of expressiveness coupled with high scores in psychological and neurophysiological parameters. Methods: We assessed the emotional facial expressions (EMFACS), psychological (anxiety, depression, alexithymia), and neurophysiological (cortisol, heart rate variability (HRV)) parameters of 25 IBS patients and 26 healthy controls (HC) while they watched fear‐eliciting movie extracts. Key Results: Overall, the task elicited an increase in state anxiety and consistent HRV responses. However, IBS patients differed from HC as they displayed more sadness and tended to display more rage. Contrary to HC, IBS patients showed an increase in heart rate and a decrease in parasympathetic regulation, reflecting an enhanced responsiveness corroborated by higher scores in depression and state anxiety. Consistent with their higher difficulty in identifying feelings, a component of alexithymia positively correlated with their expressions of rage, they were not aware of their increase in anxiety during the task, whereas HC were. No linear relationship between patients' expressions and their neurophysiological responses was found. Conclusions & Inferences: Irritable bowel syndrome patients displayed greater emotional expressiveness with negative prevalence. This reflects an emotional vulnerability potentially related to low regulation skills and underscores the importance of considering the central dysregulation hypothesis in IBS as a promising avenue of research. Abstract : Negativity is often observed in patients with irritable bowel syndrome (IBS). We investigated IBS patients' vulnerability to an emotional load associating their expressiveness with psychological and neurophysiological assessments. Patients react intensely and negatively to emotional load. Their reactivity is consistent with their neurophysiological and psychological features. Difficulty in identifying feelings tends to correlate with rage. Emotional expressiveness could be a marker of emotional reactivity in IBS. This underscores the importance of considering the hypofrontality hypothesis.